Efeitos do laser de baixa intensidade e do Biosilicato® no reparo ósseo de ratas osteopênicas - Bossini, Paulo Sérgio (Universidade Federal de São Carlos, 2010)
Osteoporosis is a systemic skeletal disease characterized by low bone density and microarchitectural deterioration of bone tissue, with consequent increase of the risk of fractures. Frequently, the lower mineral density due to osteoporosis leads to a delay in fracture healing rates and bone repair quality. Within this context, biochemical and biophysical resources have been studied in an attempt to enhance bone consolidation. Two of the most promising treatments are the use of low level laser therapy (LLLT) and bioactive materials. Several studies suggest that both resources are able to stimulate osteoblast proliferation and osteogenesis at the fracture site, promoting a greater deposition of bone mass. Thus, two studies were performed with the aim of evaluating the effects of LLLT (Ga-Al-As, 830nm, 100mW), with the fluences of 60J/cm² and 120J/cm² and a bioactive ceramic (Biosilicate®), used alone or associated on consolidation of bone defects induced in the tibiae of osteopenic rats. A total of 60 female Wistar rats (12 weeks-old, ± 250g) were submitted to ovariectomy (OVX) and, sixty days after the induction, a bone defect was performed in both tibiae of all animals. The animals were randomly divided into six groups (n=10). In the first study, the effects of LLLT on the bone repair of osteopenic rats were evaluated in three groups: group bone defect control without any treatment (GC); group bone defect irradiated with LLLT, at 60J/cm² (GL60); and group bone defect irradiated with LLLT, at 120J/cm² (GL120). The animals were submitted to laser irradiation at a single point on the bone defect for seven sessions, on alternated days. In the laser treated groups, at both fluences, it was possible to observe a greater amount of new bone formation compared to the control. Birefringence analysis demonstrated that irradiated bone defects presented greater deposition and improved the structural organization of collagen fibers, mainly in the group treated with the laser, at 120J/cm². COX-2, CBFA-1 and VEGF immunoreactivity was detected in a similar manner either 60J/cm2 or 120J/cm2 fluences. However, no differences were observed in the biomechanical analysis. Therefore, the LLLT, at the two fluences used, improved the bone repair in the tibia of osteopenic rats. In the second study, the effects of Biosilicate® associated with LLLT on bone repair in osteopenic rats were analyzed in four groups: group bone defect control without any treatment (GC); group bone defect filled with Biosilicate® (GB); group bone defect filled with Biosilicate®, irradiated with LLLT, at 60J/cm2 (GBL60); and group bone defect filled with Biosilicate®, irradiated with LLLT, at 120J/cm2 (GBL120). Biosilicate® was used in the form of particles with granulometry of 180-212μm and the treated animals were irradiated with laser at a single point on the bone defect for seven sessions, on alternated days. The results demonstrated that the LLLT, with fluences of 60J/cm² and 120J/cm² stimulated the expression of COX-2 in the circumjacent cells of the biomaterial, increased of the collagen deposition and the biomechanical bone properties. Morphometric analysis revealed that the animals with bone defects filled with Biosilicate® and irradiated with laser, at 120J/cm² showed a higher amount of newly formed bone compared to the other groups. Thus, the LLLT, mainly in fluency 120J/cm² in contact with Biosilicate® improved the bone repair process in osteopenic rats. These findings are fundamental in elucidating the biological mechanisms involved in the repair of fractures with difficult consolidation, especially those associated with bone metabolic disease processes, such as osteoporosis.
Keywords: Fisioterapia; Laser de baixa intensidade; Materiais bioativos; Osteoporose; Reparo ósseo; Ovarectomia; Bone repair; Low level laser therapy; Bioactive material; Osteoporosis; Ovariectomy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL